Development of Quick-Solidifying Foamed Concrete for Mine Fires Extinguishment and the Basic Performances Tests - KeKuo, Yuan; Yu, Gong; Shaojun, Fu; Shuanhai, Xu; Kaide, Liu; Hongdan, Yu; Shan, Gao (Frontiers in Materials, 2020)
Coal mine fires have continuously remained the primary disasters in coal mining worldwide. Cement-based inorganic foam concrete, e.g., for engineering filling and coal mine fire extinguishing, has become the first choice for responding to such fires. The objective of this study was to propose quick-solidifying foamed concrete materials based on laboratory tests, and to test the properties of these materials. The stability of a foamed slurry and solidified stone of a quick-solidifying foamed concrete were tested, along with the rheological properties, curability, shrinkage, high-temperature resistance, and cracking of the slurry during solidification. The laws and values of these characteristics were obtained. The results finally show that the quick-solidifying foamed concrete developed in this study has good performance with regard to filling and fire prevention in the large spaces of a mine.